If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -43 = 6b + 8 Reorder the terms: -43 = 8 + 6b Solving -43 = 8 + 6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6b' to each side of the equation. -43 + -6b = 8 + 6b + -6b Combine like terms: 6b + -6b = 0 -43 + -6b = 8 + 0 -43 + -6b = 8 Add '43' to each side of the equation. -43 + 43 + -6b = 8 + 43 Combine like terms: -43 + 43 = 0 0 + -6b = 8 + 43 -6b = 8 + 43 Combine like terms: 8 + 43 = 51 -6b = 51 Divide each side by '-6'. b = -8.5 Simplifying b = -8.5
| 125m-100m+38800=40200-175m | | -6(x+3)-12=17+7 | | 1.39=ln(y) | | 6a^2-a-15= | | 2y+1y+15=22 | | 6x=16-x^2 | | 1/3(3.14)(3.5^2)8 | | 6y+2-7y= | | 18-9b=-b^2 | | -14=2(u+8)-7u | | -11u--6u-2u-8=20 | | f(x)=12x-x^3 | | 6.9x-2.1=25.5 | | y-17/19=-719 | | 3k-1-6k=4k+8-9k | | 7x+26=5x+56 | | 2m^2=-7m | | -14=3(x-8)-8x | | C^2-13c+40= | | 8(w+4)-5w=20 | | -12x+5y=60 | | 4-.4x=.2x-8 | | 3x(2x+4)=6(5x+2) | | 8w+3-10w= | | 2w-11w=-12 | | 7.9=2n-5 | | y+y+x+39=180 | | X+X+10=56 | | 25a^3+20a^2+3a= | | 7x-12=4x-9 | | 131/3x2/3 | | x-5/4-x-4/5=1/2-x/10 |